Resonant third-order hyperpolarizabilities of large organic molecules - BLAU, WERNER (My University, 1987)
Resonant degenerate four-wave mixing in a number of infrared-absorbing dyeswas studied with 160-psec pulses at 1.064 ?m. Hyperpolarizabilities in the range of 10-44 to 10-42 V-2 m5 were observed. A theoretical model based on a two-band system is developed that explains the results and permits the prediction of hyperpolarizabilities from the linear spectroscopic properties.
PUBLISHED
Keywords: hyperpolarizabilities; hyperpolarizabilities